Optimization of fermentation conditions and properties of an exopolysaccharide from Klebsiella sp. H-207 and application in adsorption of hexavalent chromium. - Li Qiang; Li Yumei; Han Sheng; Liu Yingzi; Song Dongxue; Hao Dake; Wang Jiajia; Qu Yanhong; Zheng Yuxia (PLoS ONE, 2013)
The novel exopolysaccharide HZ-7 is produced by Klebsiella sp. H-207, and its fermentation conditions were optimized by response surface methodology (RSM). In this study, the optimized medium consisted of sucrose 31.93 g/L, KNO(3) 2.17 g/L and K(2)HPO(4) 5.47 g/L; while the optimized culture conditions consisted of seed age 13 h, with an inoculum size of 10.6% and incubation temperature of 28.9°C. A maximum HZ-7 yield of about 15.05 g/L was achieved under the optimized conditions using RSM and single-factor experiments. Next the exopolysaccharide HZ-7 was partially purified and characterized. The resulting product showed good properties, such as high concentration of uronic acid (41.67%), low average molecular weight (about 1.94×10(5) Da) and porous surface structure, were very advantageous to biosorption. Therefore HZ-7 was applied to absorb hexavalent chromium (Cr(VI)). The maximum adsorption efficiency (99.2%) which was obtained at an initial pH of 1.0 along with an initial Cr(VI) concentration of 20 mg/L, was not affected by ordinary metal ions and temperature. These data suggest Klebsiella sp. H-207 exopolysaccharide will be promising potential for industrial application.